The impact of the liberalisation process on the comptitiveness of firms: a case study in the Alpine regions of Switzerland - Christof Abegg; Alain Thierstein (European Regional Science Association (ERSA), 2004)
The liberalisation process has many faces. It gives rise to economic, social and cultural change. From a spatial point of view, fears are frequently expressed that liberalisation can lead to disadvantages for peripheral regions, especially in the sparsely populated Alpine region. Companies in these peripheral regions, in particular small and medium-sized enterprises (SME s) see themselves as confronted by a wide variety of challenges in maintaining their competitiveness. This paper is concerned with the effects of the liberalisation process on firms in the Swiss Alpine region. Following the introduction, a second stage will give a brief characterisation of the liberalisation process, with reference to the changes in the ideas of the state which lie behind it. The third section presents the outline of a research study which looks into the effects of the liberalisation of public services on firms in the Swiss Alpine region. Section four presents some empirical results of this study. Using the four sectors of telecommunications, the postal service, public regional transport and electricity, some liberalisation effects from the point of view of these enterprises are put forward. Section five includes contexts and conclusions: it can be seen that public services are important to enterprises in mountainous regions, but are not a decisive influence on their competitiveness. Overall, liberalisation mainly benefits large companies. The passive and cautious behaviour of small and medium-sized enterprises means that they make insufficient use of the potential advantages of liberalisation. Moreover, liberalisation contributes to an increased spatial polarisation within the Alpine region. The paper concludes by providing information on political strategies for spatial development at canton and Federal state level.
Keywords: 330